Heterologous Complementation Studies With the YscX and YscY Protein Families Reveals a Specificity for Yersinia pseudotuberculosis Type III Secretion - Gurung, Jyoti M.; Amer, Ayad A. A.; Francis, Monika K.; Costa, Tiago R. D.; Chen, Shiyun; Zavialov, Anton V.; Francis, Matthew S. (Frontiers in Cellular and Infection Microbiology, 2018)
Type III secretion systems harbored by several Gram-negative bacteria are often used to deliver host-modulating effectors into infected eukaryotic cells. About 20 core proteins are needed for assembly of a secretion apparatus. Several of these proteins are genetically and functionally conserved in type III secretion systems of bacteria associated with invertebrate or vertebrate hosts. In the Ysc family of type III secretion systems are two poorly characterized protein families, the YscX family and the YscY family. In the plasmid-encoded Ysc-Yop type III secretion system of human pathogenic Yersinia species, YscX is a secreted substrate while YscY is its non-secreted cognate chaperone. Critically, neither an yscX nor yscY null mutant of Yersinia is capable of type III secretion. In this study, we show that the genetic equivalents of these proteins produced as components of other type III secretion systems of P. aeruginosa (PscX and PscY), Aeromonas species (AscX and AscY), Vibrio species (VscX and VscY), and Photorhabdus luminescens (SctX and SctY) all possess an ability to interact with its native cognate partner and also establish cross-reciprocal binding to non-cognate partners as judged by a yeast two-hybrid assay. Moreover, a yeast three-hybrid assay also revealed that these heterodimeric complexes could maintain an interaction with YscV family members, a core membrane component of all type III secretion systems. Despite maintaining these molecular interactions, only expression of the native yscX in the near full-length yscX deletion and native yscY in the near full-length yscY deletion were able to complement for their general substrate secretion defects. Hence, YscX and YscY must have co-evolved to confer an important function specifically critical for Yersinia type III secretion.